FENOMENA PERDAGANGAN PEREMPUAN DENGAN MODUS PROSTITUSI TERSELUBUNG DI CAFÉ KARAOKE ( STUDI KASUS DI KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU) - Vanessa, Tania; Sobri (Sisi Lain Realita, 2024)
Phenomenon is defined as the supposed state of a thing, a special condition that is connected to a person or thing. Woman trafficking is one of the hidden modes of prostitution and it is a crime against women. The rise of this phenomenon also occurs in karaoke cafes, we can found out that women will work as karaoke sex guides and then make these women as commercial workers (CSWs). Prostitution is the activity of someone who sells her own body, honor and personality to many people to satisfy their lust with imbalance or payment. This study aims to determine the phenomenon of women trafficking with hidden prostitution modes in karaoke cafes that occurred in Ujung Batu District, Rokan Hulu Regency. This type of research is a qualitative research with a descriptive approach. The results of this study explain that the women in the cafe only worked as guides first but because the buyer asked women who can be rented and invited to open rooms, the cafe provided women commercial sex workers (CSWs) but it is only given to certain customers.